2014
DOI: 10.1016/j.expneurol.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of sleep/wake changes and cataplexy-like behaviors in orexin/ataxin-3 transgenic narcoleptic mice across the disease onset

Abstract: Sleep and behavioral monitoring of young mice is necessary for understating the progress of symptoms in congenital and acquired diseases associated with sleep and movement disorders. In the current study, we have developed a non-invasive sleep monitoring system that identifies wake and sleep patternsof newborn mice using a simple piezoelectric transducer (PZT). Using this system, we have succeeded in detecting age-dependent occurrences and changes in sleep fragmentation of orexin/ataxin-3 narcoleptic mice (a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Though mouse sleep can be measured using other noninvasive approaches, EF sensor recordings have the additional ability to simultaneously quantify other motor behaviors such as ventilation profiles in non-REM and REM sleep, grooming, locomotion, eating, and drinking using only a frequency-based features of a single voltage channel. 31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though mouse sleep can be measured using other noninvasive approaches, EF sensor recordings have the additional ability to simultaneously quantify other motor behaviors such as ventilation profiles in non-REM and REM sleep, grooming, locomotion, eating, and drinking using only a frequency-based features of a single voltage channel. 31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient. Of the published studies capable of noninvasively measuring 3state sleep architecture, the reported overall accuracies to EEG/EMG range from 84% to 91%, 10,11,20,21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no prescreening method prior to EEG/EMG studies for sorting mice that are highly symptomatic for narcolepsy. In a previous study, Atax mice were monitored with piezoelectric detection of movement and heartrate for a few hours during the light period, but the algorithm for autoscoring was only 73% accurate against manual EEG scoring (14) and missed the time of day in which cataplexy and sleep/wake fragmentation occurs most frequently (20).…”
Section: Introductionmentioning
confidence: 98%
“…The use of non-invasive proxy-measures of sleep/wake, such as actigraphy, plethysmography, or heartbeat rate correlates of arousal states instead of traditional polysomnography, can expedite sleep/wake determination in rodents (9)(10)(11)(12)(13)(14). In particular, the use of a highly sensitive motion detector (piezoelectric sensor) on the cage floor to monitor gross motor activity, together with breathing patterns during periods of behavioral quiescence, yields unsupervised sleep/wake detection with 90% accuracy vs. manual EEG scoring (15).…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al (2010) used a piezoelectric transducer to monitor mice and documented rapid increases in breathing rate during sleep with atonic posture, presumably in REM . They subsequently used this piezoelectric system to differentiate REM from NREM and Wake , but on the basis of immobility and perceived heart rate signals, in a small sample of wild type mice (Sato et al 2014). …”
Section: Introductionmentioning
confidence: 99%